Bullying in Physical Education: Awareness of Physical Education Teachers - Sağin Ahmet Enes; Uğraş Sinan; Güllü Mehmet (Sciendo, 2022)
This study investigates how physical education (PE) teachers make sense of peer bullying, which types of behaviors they associate with peer bullying, their opinions about these behaviors, and methods for preventing bullying. The study group consisted of 18 PE teachers. The interview technique was used as a qualitative research method in the study. The data obtained after one-on-one interviews were analyzed through content analysis. According to the data obtained, PE teachers are the most important variable in the decrease or increase of peer bullying in classes. However, PE classes provide a suitable environment for the emergence of peer bullying. Additionally, bullying caused by the individual characteristics of students and environmental reasons can increase in schools, and there are generally no collective intervention programs within schools to prevent it. According to the teachers' opinions, some of the important results are that students who are exposed to bullying experience the same fear every week in PE lessons, and although it is known that the majority of them do not want to participate in the activity in order to avoid being bullied, no solution can be found.